2002
DOI: 10.1046/j.1365-2664.2002.00696.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of induced sterility on the territorial behaviour and survival of foxes

Abstract: Summary1. This paper reports on the behavioural effects of surgical sterilization when used to simulate immunocontraception in free-ranging female foxes Vulpes vulpes . 2. During 3 years of trapping, 348 male and female foxes were fitted with transmitters in two treatment (females sterilized) and two untreated areas. 3. Radio-tracking indicated that sterile and fertile vixens maintained similar-sized territories during the breeding season, but that sterile females were possibly more likely to share their terri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…PZP-based immunocontraceptives increased lifespan and body conditions of mares Kirkpatrick and Turner 2007), tubal ligation increased survival in rabbits (Twigg et al 2000;Williams et al 2007) and GonaCon improved body condition of deer (Gionfriddo et al 2011b). Conversely, Saunders et al (2002) observed no differences in survival, dispersal or territory size of surgically sterilised foxes compared with fertile foxes, although sterilised vixens were more likely than fertile females to share their territories with each other.…”
Section: Fertility-control Impact On Wildlife Populationsmentioning
confidence: 50%
“…PZP-based immunocontraceptives increased lifespan and body conditions of mares Kirkpatrick and Turner 2007), tubal ligation increased survival in rabbits (Twigg et al 2000;Williams et al 2007) and GonaCon improved body condition of deer (Gionfriddo et al 2011b). Conversely, Saunders et al (2002) observed no differences in survival, dispersal or territory size of surgically sterilised foxes compared with fertile foxes, although sterilised vixens were more likely than fertile females to share their territories with each other.…”
Section: Fertility-control Impact On Wildlife Populationsmentioning
confidence: 50%
“…Their position in the top of the food webs and their large potential impact on different human activities (game, agriculture, etc..., Saunders et al 1995;Reynolds. and Tapper 1996;Moore et al 1999) make this group especially significant in conservation and management actions.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the long-term effectiveness of a contraceptive is needed to predict the effects of fertility control, in terms of proportion of infertile animals and longevity of effect, on population size. For territorial or hierarchically structured species, contraception-induced changes in social behaviour, such as decreased aggressiveness, could lead to disruption of social hierarchies and spacing behaviour and, in turn, affect the impact of fertility control on a population (Saunders et al 2002;Crawford et al 2011). The potential impact of a contraceptive on social behaviour should thus be evaluated before fertility control is used to manage wildlife populations.…”
Section: Introductionmentioning
confidence: 99%